Reality denial in the novel "A Monster Calls (2011)" by Patrick Ness - Muhammad Fajar; Kurnia Ningsih (English Language and Literature, 2021)
This is an analysis of the novel A Monster Calls (2011) written by Patrick Ness. The problem of this study is how far the novel A Monster Calls (2011) expose the issue about reality denial. The purpose of this study is to seek how far the characters, twelve years old child, setting, and plot (conflict) reflects the issue about reality denial. This analysis deals with the concept of defense mechanism by Sigmund Freud. The result of this analysis shows that the protagonist does the reality denial to refuse the unpleasant things in his family. This can be seen through his behavior and attitude.